Novel thermoplastic elastomer triblocks of a soft polyisobutylene midblock connected to two hard PMMA stereocomplex outer blocks - Kennedy, Joseph P; Price, Jack L; Koshimura, Katsuo (Macromolecules, 1991)
The synthesis, characterization, and select physical properties of novel thermoplastic elastomers (TPEs) consisting of two hard poly(methyl methacrylate) (PMMA) stereocomplex outer blocks flanking a soft polyisobutylene (PIB) midblock are discussed. The preparation of the starting material, a PMMA-b-PIB-b--PMMA triblock with syndiotactic PMMA (sPMMA) outer blocks, was the subject of a previous publication; this report focuses on the preparation of PMMA stereocomplexes as outer blocks by blending isotactic PMMA (iPMMA) with the sPMMA of the triblocks. Sterocomplex formation was demonstrated by DSC studies. The melting temperature of iPMMA/sPMMA stereocomplexes (170-200 deg C) is affected by the relative amounts of the i- and sPMMA in the outer blocks and is much higher than either of the T sub g s of the i- and sPMMA ( approx 52 and approx 102 deg C, respectively) components. The blending solvent, i- and sPMMA molecular weights, and annealing affect stereocomplexation. Stereocomplexation elevates the T sub g of these TPEs and leads to enhanced tensile strengths, moduli, and elongations combined with desirably low hardness values.